Preparation and application of succinonitrile-functionalized polyethylene oxide

CN117683224BActive Publication Date: 2026-10-27XI AN JIAOTONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311692508.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-11
Publication Date
2026-10-27
Estimated Expiration
2043-12-11

AI Technical Summary

Technical Problem

[0004]然而,这种策略存在潜在的弊端:由于增塑剂通常与高分子链段之间不存在有效的化学键合作用,因此在一段时间的弛豫后,聚合物内部的增塑剂会向表面渗出,这些增塑剂大多数易燃且对人体有害,将带来潜在的安全风险

Benefits of technology

[0023](1)本发明的合成条件简单温和、绿色,仅需通过混合、搅拌、光照等步骤就能得到丁二腈官能团化的聚环氧乙烷离子,不需要繁琐的聚合反应步骤。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004599646530000011
    Figure HDA0004599646530000011
  • Figure HDA0004599646530000012
    Figure HDA0004599646530000012
  • Figure HDA0004599646530000013
    Figure HDA0004599646530000013
Patent Text Reader

Abstract

The application relates to a preparation method of a succindinitrile functionalized polyethylene oxide and application thereof, and the preparation method specifically comprises the following steps: covalently connecting a succindinitrile molecular structure with excellent ion dissociation and conduction characteristics to a molecular chain of polyethylene oxide, avoiding hidden troubles such as liquid leakage caused by traditional direct addition of a succindinitrile plasticizer, and effectively enhancing the ion conduction capacity and adhesion of the polyethylene oxide, so that the normal use of a solid-state alkali metal battery at room temperature can be met, and therefore the material can be applied to a solid-state polymer electrolyte; in addition, the excellent adhesion and ion conduction characteristics enable the material to also serve as an electrode or a binder for inorganic ceramic particle film preparation; the succindinitrile functionalized polyethylene oxide has wide application prospects in the fields of energy and chemical industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of novel polymer material preparation technology, and specifically relates to the preparation and application of butadionitrile-functionalized polyethylene oxide. Background Technology

[0002] Polyethylene oxide (PEO) is widely used as a solid electrolyte and binder in solid-state metal batteries due to its excellent flexibility, processability, ionic conductivity, and contact stability with active metals. PEO is composed of linear ethylene oxide repeating units (-CH2-CH2-O-), with a relative molecular weight typically between 200 and 5,000,000. The numerous ether oxygen structures on the molecular chain endow the polymer matrix with strong electronegativity, making it easy for this polymer to coordinate or hydrogen bond with metal cations and most free hydroxyl groups on its surface. Generally, only when the molecular weight is above 100,000 can PEO maintain a certain level of mechanical strength and be used in the aforementioned applications. However, at higher molecular weights, the single constituent unit and simple linear structure make the polymer highly susceptible to crystallization, leading to impaired chain movement at room temperature and slow interactions with metal ions, thus hindering the material's unique ionic conductivity properties.

[0003] To address the aforementioned issues, the current mainstream optimization method involves adding plasticizers to polyethylene oxide polymers. This improves the polymer's crystallinity and enhances the overall ion coordination and conductivity of the material. Plasticizers are typically small-molecule compounds that behave as liquids at room temperature. Therefore, their direct addition to the polymer weakens intermolecular forces and disrupts crystalline regions, significantly enhancing the ion dissociation, conductivity, and adhesive properties of polyethylene oxide.

[0004] However, this strategy has potential drawbacks: because plasticizers typically do not have effective chemical bonds with polymer segments, after a period of relaxation, plasticizers inside the polymer can seep to the surface. Most of these plasticizers are flammable and harmful to humans, posing potential safety risks. Furthermore, plasticizers can undergo phase separation within the polymer, leading to an irreversible decline in the originally enhanced properties.

[0005] Among various plasticizers, succinic anhydride has been extensively studied due to the strong polarity of the two cyano groups in its molecule, which enable it to coordinate with metal cations such as lithium ions and sodium ions and to form potential hydrogen bonds. Patent CN113299985A discloses a method for preparing a succinic anhydride-based bilayer composite polymer electrolyte and its application. However, directly adding succinic anhydride to the polymer cannot avoid the potential problems brought about by the plasticizing strategy. Summary of the Invention

[0006] In order to overcome the shortcomings of the prior art, the present invention aims to provide a method for preparing and applying succinic acid-functionalized polyoxyethylene ions. The novel succinic acid-functionalized polyoxyethylene ions have excellent ion conduction and adhesion properties, and can be used in solid electrolytes of lithium, sodium, and potassium ion batteries. They can also be used as binders in the preparation of lithium, sodium, and potassium battery electrodes or in the pressing of inorganic ceramic particles.

[0007] To achieve the above objectives, the technical solution of the present invention is as follows:

[0008] A method for preparing butadionitrile-functionalized polyethylene oxide includes the following steps:

[0009] (I) Catalyst Preparation

[0010] (1) Dissolve 124.3–187.5 mg of anhydrous ferric chloride and 205.4–310.5 mg of tetrabutylammonium chloride in 0.5–3 mL of anhydrous acetonitrile to obtain a mixed solution;

[0011] (2) Stir the above mixed solution evenly under a nitrogen atmosphere;

[0012] (3) The solvent obtained in step (2) is evaporated by rotary evaporation, and the crude product is recrystallized in hexane / ethyl acetate. The recrystallized product is the catalyst used in the subsequent reaction.

[0013] (II) Preparation of polyoxyethylene with butadiene nitrile functionalization

[0014] (1) Add 220-440 mg of raw polyethylene oxide powder, 78-234 mg of fumaric acid reactant monomer, and 4.4-13.2 mg of catalyst to a sealed tube and transfer it to a nitrogen atmosphere;

[0015] (2) Add 10-50 mL of anhydrous acetonitrile to the sealing tube under a nitrogen atmosphere, seal the tube and stir until fully dissolved to obtain a well dissolved mixed solution.

[0016] (3) Take out the dissolved mixture and stir it under the irradiation of a 390nm LED lamp for 2 to 24 hours;

[0017] (4) After the reaction is complete, the mixed solution obtained in step (3) is added dropwise to a precipitation bath in which anhydrous acetonitrile and diethyl ether are in a volume ratio of 1:4 to 8 for precipitation. The product is collected by filtration, redissolved in anhydrous acetonitrile and precipitated again in the precipitation bath. This step is repeated three times. The product is collected and dried, which is the prepared product, butadionitrile-functionalized polyoxyethylene.

[0018] The original polyethylene oxide powder comprises polyethylene oxides with different molecular weights ranging from 100,000 to 2,000,000 relative molecular weights.

[0019] An application of a butadionitrile-functionalized polyethylene oxide is disclosed in solid polymer electrolytes, and it is used in solid lithium, sodium, and potassium-ion batteries according to the differences in cationic salts.

[0020] An application of a butadienenitrile-functionalized polyethylene oxide as a binder in the preparation of electrodes for lithium, sodium, and potassium-ion batteries.

[0021] An application of a butadienenitrile-functionalized polyethylene oxide as a binder in the process of pressing inorganic ceramic powders with lithium, sodium, and potassium ion conductivity into films.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] (1) The synthesis conditions of the present invention are simple, mild and green. Only steps such as mixing, stirring and light irradiation are needed to obtain polyoxyethylene ions with succinic acrylonitrile functionalization, without the need for complicated polymerization reaction steps.

[0024] (2) This material fixes small molecules onto the polymer through covalent bonds, which has good stability and will not cause problems such as exudation, leakage or phase separation that may occur with the addition of plasticizers.

[0025] (3) Due to the influence of the succinate structure, polyoxyethylene with succinate functional groups has excellent ion conductivity and higher ion conductivity than unmodified polyoxyethylene with the same molecular weight. Therefore, it exhibits excellent performance in solid-state batteries.

[0026] (4) The succinic acid functional groups on the ethylene oxide molecular chain accelerate the chain segment movement and polarity inside the polymer, so the modified material exhibits excellent bonding properties.

[0027] In summary, inspired by the succinic acrylonitrile structure, this invention prepares a novel polyoxyethylene with succinic acrylonitrile functionalization by directly covalently attaching the succinic acrylonitrile structure to the molecular chain of polyoxyethylene, thereby significantly improving polymer performance while effectively solving various problems caused by plasticization. Attached Figure Description

[0028] Figure 1 This is the chemical reaction equation for the catalyst during the preparation process.

[0029] Figure 2 The chemical reaction equation for preparing butadionitrile-functionalized polyethylene oxide.

[0030] Figure 3 Differential scanning calorimetry analysis of the butadionitrile-functionalized polyethylene oxide solid electrolyte of Example 1 of the present invention.

[0031] Figure 4 The X-ray diffraction patterns of the poly(ethylene oxide) solid electrolyte before and after functionalization of succinic anionylene in Example 2 of the present invention are shown.

[0032] Figure 5 This is the electrochemical window of the butadionitrile-functionalized polyethylene oxide solid electrolyte of Example 3 of the present invention.

[0033] Figure 6 The results show the temperature-dependent ionic conductivity of the butadiene-functionalized polyethylene oxide solid electrolyte in Example 3 of this invention.

[0034] Figure 7 The image shows the constant potential current-time curve and impedance changes before and after the butadiene nitrile-functionalized polyethylene oxide solid electrolyte of Example 3 of the present invention.

[0035] Figure 8 The cycling performance of the butadionitrile-functionalized polyethylene oxide solid electrolyte of Example 4 of the present invention in a LiFePO4 / / Li full cell at 45°C.

[0036] Figure 9 The cycling performance of the butadionitrile-functionalized polyethylene oxide solid electrolyte of Example 4 of the present invention in a LiFePO4 / / Li full cell at 25°C.

[0037] Figure 10 The adhesion properties of the butadiene-functionalized polyethylene oxide in Example 5 of this invention are shown.

[0038] Figure 11 This is a graph showing the changes in the adhesion properties of butadiene-functionalized polyethylene oxide in Example 5 of the present invention.

[0039] Figure 12 This is a photograph of the electrode sheet obtained by scraping with butadiene-functionalized polyethylene oxide as a binder, as shown in Example 5 of the present invention.

[0040] Figure 13 The AC impedance change of the alumina electrolyte sheet before and after using succinic anionylene functionalized polyethylene oxide in Example 6 of the present invention is shown. Detailed Implementation

[0041] The present invention will be further described in detail below with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Where specific techniques or conditions are not specified in the embodiments, they are performed in accordance with the techniques or conditions described in the literature in the art or according to the product instructions. All raw materials and chemical reagents used are of analytical grade.

[0042] Example 1

[0043] This embodiment includes the following steps:

[0044] (I) Catalyst Preparation

[0045] (1) Dissolve 124.3 mg of anhydrous ferric chloride and 310.5 mg of tetrabutylammonium chloride in 3 mL of anhydrous acetonitrile;

[0046] (2) Stir the above mixture in a glove box filled with nitrogen for 45 minutes;

[0047] (3) The solvent of the above solution was rotary evaporated, and the crude product was recrystallized in hexane / ethyl acetate. The recrystallized product was used as the catalyst in the subsequent reaction. The entire reaction process is shown in [reference needed]. Figure 1 .

[0048] (II) Preparation of polyoxyethylene with butadiene nitrile functionalization

[0049] (1) Add 220 mg of raw polyethylene oxide powder (relative molecular weight of 600,000), 78 mg of fumaric acid reactant monomer, and 4.4 mg of catalyst to a 100 mL sealed tube and transfer it to a glove box filled with nitrogen.

[0050] The original polyethylene oxide powder includes polyethylene oxides with different molecular weights ranging from 100,000 to 2,000,000. In addition, polyethylene oxide, polyethylene glycol, etc. have the same molecular formula as polyethylene oxide but different names. In actual use, the difference should not be based on the name but on the actual molecular formula and specific molecular weight to determine whether it is the same as the original polyethylene oxide.

[0051] (2) Add 10 mL of anhydrous acetonitrile to the above-mentioned sealing tube in the glove box, seal the sealing tube, and stir until fully dissolved;

[0052] (3) Remove the dissolved mixture from the glove box and stir it under a 390nm LED light for 4 hours; see the reaction process below. Figure 2 ;

[0053] (4) After the reaction is complete, the above mixed solution is slowly added dropwise to a precipitation bath of anhydrous acetonitrile and diethyl ether at a volume ratio of 1:8 (anhydrous acetonitrile: diethyl ether) for precipitation. The product is collected by filtration, redissolved in 10 mL of anhydrous acetonitrile and precipitated again in the precipitation bath. The above operation is repeated three times. The product is collected and dried in a vacuum oven at 40°C for 24 hours for later use. This product is the polyoxyethylene succinate functionalized by butadiene nitrile.

[0054] The product obtained in this embodiment is used in the solid electrolyte of a solid sodium-ion battery. The specific steps are as follows:

[0055] (1) Add 440 mg of butadionitrile-functionalized polyethylene oxide and 87.21 mg of sodium perchlorate to a beaker, then add 10 mL of anhydrous acetonitrile as a solvent and stir to fully dissolve the polymer.

[0056] (2) Pour the above solution onto a polytetrafluoroethylene plate to evaporate the solvent, leave the solvent at room temperature for 6 hours, and then transfer it to a vacuum oven at 50°C for 24 hours.

[0057] (3) Remove the dried electrolyte membrane and cut it into appropriate sizes for testing.

[0058] The thermodynamic properties of the solid electrolyte membrane obtained in this embodiment were tested.

[0059] Based on differential scanning calorimetry (DSC), a precise mass of polymer solid electrolyte was weighed and then placed in a DSC instrument to test the endothermic and exothermic changes of the solid electrolyte. The results are as follows: Figure 3 As shown, the melting temperature of the polyoxyethylene solid electrolyte with succinic anhydride functionalization is 47.3℃, and the crystallization temperature is only 25.1℃, indicating that the solid electrolyte has good flexibility at room temperature and ensures high ionic conductivity at room temperature.

[0060] For the preparation of solid electrolyte membranes for sodium and potassium ion batteries, it is only necessary to replace the lithium perchlorate mentioned above with inorganic salts containing sodium or potassium ions, such as sodium perchlorate or potassium hexafluorophosphate.

[0061] Example 2

[0062] This embodiment includes the following steps:

[0063] (I) Catalyst Preparation

[0064] (1) Dissolve 137.2 mg of anhydrous ferric chloride and 228.1 mg of tetrabutylammonium chloride in 2.5 mL of anhydrous acetonitrile;

[0065] (2) Stir the above mixture in a glove box filled with nitrogen for 30 minutes;

[0066] (3) The solvent of the above solution was rotary evaporated, and the crude product was recrystallized in hexane / ethyl acetate. The recrystallized product was used as the catalyst in the subsequent reaction. The entire reaction process is shown in [reference needed]. Figure 1 .

[0067] (II) Preparation of polyoxyethylene with butadiene nitrile functionalization

[0068] (1) Add 330 mg of raw polyethylene oxide powder (relative molecular weight of 600,000), 156 mg of fumaric acid reactant monomer, and 4.4 mg of catalyst to a 100 mL sealed tube and transfer it to a glove box filled with nitrogen.

[0069] (2) Add 30 mL of anhydrous acetonitrile to the above-mentioned sealing tube in the glove box, seal the sealing tube, and stir until fully dissolved;

[0070] (3) Take out the above dissolved mixture from the glove box and stir it for 6 hours under the irradiation of a 390nm LED lamp;

[0071] (4) After the reaction is complete, the above mixed solution is slowly added dropwise to a precipitation bath of anhydrous acetonitrile and diethyl ether at a volume ratio of 1:7 (anhydrous acetonitrile: diethyl ether) for precipitation. The product is collected by filtration, redissolved in 10 mL of anhydrous acetonitrile and precipitated again in the precipitation bath. The above operation is repeated three times. The product is then collected and dried in a vacuum oven at 40°C for 24 hours for later use.

[0072] The product obtained in this embodiment is used in the solid electrolyte of a solid potassium-ion battery. The specific steps are as follows:

[0073] (1) Add 440 mg of succinate-functionalized polyethylene oxide and 106.6 mg of potassium hexafluorophosphate to a beaker, then add 10 mL of anhydrous acetonitrile as a solvent and stir to fully dissolve the polymer.

[0074] (2) Pour the above solution onto a polytetrafluoroethylene plate to evaporate the solvent, leave the solvent at room temperature for 6 hours, and then transfer it to a vacuum oven at 50°C for 24 hours.

[0075] (3) Remove the dried electrolyte membrane and cut it to an appropriate size for testing. The crystallinity of the solid electrolyte membrane obtained in this embodiment is tested using the following method:

[0076] (1) X-ray diffraction pattern. A 19mm diameter disc was cut from a solid polyethylene oxide electrolyte membrane. The membrane was gently placed on the test stage. The test angle was 10°–80°, and the test rate was 5° / minute. The resulting X-ray diffraction pattern is shown in the figure. Figure 4As can be seen from the figure, the crystallinity of poly(ethylene oxide) decreases significantly after functionalization of succinic anion. This decrease in crystallinity ensures that potassium ions inside the polymer can be transported at a faster rate.

[0077] Example 3

[0078] This embodiment includes the following steps:

[0079] (I) Catalyst Preparation

[0080] (1) Dissolve 151.6 mg of anhydrous ferric chloride and 253.5 mg of tetrabutylammonium chloride in 2 mL of anhydrous acetonitrile;

[0081] (2) Stir the above mixture in a glove box filled with nitrogen for 60 minutes;

[0082] (3) The solvent of the above solution was rotary evaporated, and the crude product was recrystallized in hexane / ethyl acetate. The recrystallized product was used as the catalyst in the subsequent reaction. The entire reaction process is shown in [reference needed]. Figure 1 .

[0083] (II) Preparation of polyoxyethylene with butadiene nitrile functionalization

[0084] (1) Add 400 mg of raw polyethylene oxide powder (relative molecular weight of 300,000), 178 mg of fumaric acid reactant monomer, and 8.8 mg of catalyst to a 100 mL sealed tube and transfer it to a glove box filled with nitrogen.

[0085] (2) Add 25 mL of anhydrous acetonitrile to the above-mentioned sealing tube in the glove box, seal the sealing tube, and stir until fully dissolved;

[0086] (3) Take out the above-dissolved mixed solution from the glove box and stir it for 5 hours under the irradiation of a 390nm LED lamp;

[0087] (4) After the reaction is complete, the above mixed solution is slowly added dropwise to a precipitation bath of anhydrous acetonitrile and diethyl ether at a volume ratio of 1:6 (anhydrous acetonitrile: diethyl ether) for precipitation. The product is collected by filtration, redissolved in 10 mL of anhydrous acetonitrile and precipitated again in the precipitation bath. The above operation is repeated three times. The product is then collected and dried in a vacuum oven at 40°C for 24 hours for later use.

[0088] The product obtained in this embodiment is used in the solid electrolyte of a solid potassium-ion battery. The specific steps are as follows:

[0089] (1) Add 440 mg of succinate-functionalized polyethylene oxide and 106.3 mg of potassium hexafluorophosphate to a beaker, then add 10 mL of anhydrous acetonitrile as a solvent and stir to fully dissolve the polymer.

[0090] (2) Pour the above solution onto a polytetrafluoroethylene plate to evaporate the solvent, leave the solvent at room temperature for 6 hours, and then transfer it to a vacuum oven at 50°C for 24 hours.

[0091] (3) Remove the dried electrolyte membrane and cut it into appropriate sizes for testing.

[0092] The solid electrolyte membrane obtained in this embodiment was subjected to electrochemical tests, and the test methods are as follows:

[0093] (1) Electrochemical window testing. A succinic anionylene-functionalized polyethylene oxide solid electrolyte membrane was cut into 19mm diameter discs. In an argon-filled glove box (moisture content < 0.1ppm, oxygen content < 0.1ppm), a battery was assembled using the following configuration: negative electrode shell + lithium sheet + solid electrolyte membrane + stainless steel sheet + positive electrode shell. Linear sweep voltammetry was performed on an electrochemical workstation, with a test range of open-circuit voltage to 6V. The test results are as follows: Figure 5 As shown, this result indicates that the polyoxyethylene solid electrolyte membrane with succinic anhydride functionalization has an oxidation potential of 4.75V, enabling it to operate safely and stably in lithium-ion batteries and avoiding the oxidative decomposition of the solid electrolyte by high-voltage cathode materials.

[0094] (2) Test of ionic conductivity over time. A succinic acid-functionalized polyethylene oxide electrolyte membrane was cut into 19mm diameter discs, clamped between two stainless steel sheets, and kept at different temperatures for 30 minutes. The impedance was then measured, and the ionic conductivity at the corresponding temperatures was calculated. The test results are as follows: Figure 6 As shown.

[0095] (3) Lithium-ion transference number test. The succinic anion-functionalized polyethylene oxide solid electrolyte membrane was cut into 19mm diameter discs. In an argon-filled glove box (moisture content < 0.1 ppm, oxygen content < 0.1 ppm), a battery was assembled using the following configuration: negative electrode shell + lithium plate + solid electrolyte membrane + lithium plate + positive electrode shell. The initial impedance of the battery was first measured in an electrochemical workstation. Then, the change in current over time was measured at a constant potential of 10mV. The test was terminated after the current stabilized. Finally, the stable impedance of the battery was measured. The test results are shown below. Figure 7 This result indicates that the succinic anion-functionalized polyethylene oxide solid electrolyte possesses a higher lithium-ion transference number, thereby improving the battery's cycle stability and capacity retention.

[0096] Example 4

[0097] This embodiment includes the following steps:

[0098] (I) Catalyst Preparation

[0099] (1) Dissolve 162.3 mg of anhydrous ferric chloride and 276.5 mg of tetrabutylammonium chloride in 1.5 mL of anhydrous acetonitrile;

[0100] (2) Stir the above mixture in a glove box filled with nitrogen for 50 minutes;

[0101] (3) The solvent of the above solution was rotary evaporated, and the crude product was recrystallized in hexane / ethyl acetate. The recrystallized product was used as the catalyst in the subsequent reaction. The entire reaction process is shown in [reference needed]. Figure 1 .

[0102] (II) Preparation of polyoxyethylene with butadiene nitrile functionalization

[0103] (1) Add 360 mg of raw polyethylene oxide powder (relative molecular weight of 300,000), 143 mg of fumaric acid reactant monomer, and 13.4 mg of catalyst to a 100 mL sealed tube and transfer it to a glove box filled with nitrogen.

[0104] (2) Add 35 mL of anhydrous acetonitrile to the above-mentioned sealing tube in the glove box, seal the sealing tube, and stir until fully dissolved;

[0105] (3) Take out the above-dissolved mixed solution from the glove box and stir it for 10 hours under the illumination of a 390nm LED lamp;

[0106] (4) After the reaction is complete, the above mixed solution is slowly added dropwise to a precipitation bath of anhydrous acetonitrile and diethyl ether at a volume ratio of 1:5 (anhydrous acetonitrile: diethyl ether) for precipitation. The product is collected by filtration, redissolved in 10 mL of anhydrous acetonitrile and precipitated again in the precipitation bath. The above operation is repeated three times. The product is then collected and dried in a vacuum oven at 40°C for 24 hours for later use.

[0107] The product obtained in this embodiment is used in the solid electrolyte of a solid lithium-ion battery. The specific steps are as follows:

[0108] (1) Add 440 mg of functionalized polyethylene oxide powder and 78.43 mg of lithium perchlorate to a beaker, then add 10 mL of anhydrous acetonitrile as a solvent and stir to fully dissolve the polymer.

[0109] (2) Pour the above solution onto a polytetrafluoroethylene plate to evaporate the solvent, leave the solvent at room temperature for 6 hours, and then transfer it to a vacuum oven at 50°C for 24 hours.

[0110] (3) Remove the dried electrolyte film and cut it to an appropriate size for testing. The specific steps for applying the polymer solid electrolyte prepared in this embodiment in lithium-ion batteries are as follows:

[0111] (1) Preparation of positive electrode sheet: 90% lithium iron phosphate powder, 5% carbon black and 5% polyvinylidene fluoride (binder) were added to N-methylpyrrolidone and ball-milled for 2 hours to form a viscous slurry, which was then coated onto aluminum foil. The slurry was placed in a vacuum drying oven and vacuum dried at 120°C for 12 hours.

[0112] (2) Assembly of button batteries: In a glove box filled with argon gas (moisture content < 0.1 ppm, oxygen content < 0.1 ppm), the batteries are assembled in the following order: positive electrode shell + positive electrode plate + solid electrolyte + lithium plate + gasket + spring plate + negative electrode shell.

[0113] (3) The assembled battery was charged and discharged within the range of 2.8 to 4V. The temperature of the incubator in which the battery was subjected to high temperature and room temperature charge and discharge cycle tests was set to 45℃ and 25℃, respectively. Figure 8 The discharge specific capacity curve and coulombic efficiency of the lithium-ion battery using the modified polyethylene oxide solid electrolyte at 0.1C current density and 45℃ demonstrate that it has good electrochemical cycle stability and high coulombic efficiency at higher temperatures. Figure 9 The discharge specific capacity curve of the lithium-ion battery using succinate-functionalized polyethylene oxide solid electrolyte at 0.05C current density and 25℃ indicates good electrochemical cycling stability at room temperature.

[0114] Example 5

[0115] This embodiment includes the following steps:

[0116] (I) Catalyst Preparation

[0117] (1) Dissolve 187.5 mg of anhydrous ferric chloride and 205.4 mg of tetrabutylammonium chloride in 0.5 mL of anhydrous acetonitrile;

[0118] (2) Stir the above mixture in a glove box filled with nitrogen for 15 minutes;

[0119] (3) The solvent of the above solution was rotary evaporated, and the crude product was recrystallized in hexane / ethyl acetate. The recrystallized product was used as the catalyst in the subsequent reaction. The entire reaction process is shown in [reference needed]. Figure 1 .

[0120] (II) Preparation of polyoxyethylene with butadiene nitrile functionalization

[0121] (1) Add 500 mg of raw polyethylene oxide powder (relative molecular weight of 300,000), 144 mg of fumaric acid reactant monomer, and 12.4 mg of catalyst to a 100 mL sealed tube and transfer it to a glove box filled with nitrogen.

[0122] (2) Add 45 mL of anhydrous acetonitrile to the above-mentioned sealing tube in the glove box, seal the sealing tube, and stir until fully dissolved;

[0123] (3) Take out the above dissolved mixture from the glove box and stir it for 6 hours under the irradiation of a 390nm LED lamp;

[0124] (4) After the reaction is complete, the above mixed solution is slowly added dropwise to a precipitation bath containing anhydrous acetonitrile and diethyl ether at a volume ratio of 1:4 (anhydrous acetonitrile: diethyl ether) for precipitation. The product is collected by filtration, redissolved in 10 mL of anhydrous acetonitrile and precipitated again in the precipitation bath. The above operation is repeated three times. The product is then collected and dried in a vacuum oven at 40°C for 24 hours for later use.

[0125] The modified polyethylene oxide obtained in this embodiment can be used as a binder in electrode materials. The preparation of these battery electrode materials usually differs only in the active material. Therefore, the preparation of lithium-ion lithium iron phosphate cathode is described as an example, and the specific steps are as follows:

[0126] (1) Mix 60 mg of lithium iron phosphate powder, 20 mg of functionalized polyethylene oxide powder, 10 mg of conductive carbon black and 10 mg of lithium perchlorate in 1 mL of anhydrous acetonitrile.

[0127] (2) The above mixed solution was stirred for 2 hours under magnetic stirring at 500 rpm;

[0128] (3) Apply the above mixture onto aluminum foil with a scraper and place it in a vacuum oven at 60°C for 12 hours;

[0129] (4) Cut the above-mentioned electrode sheets into appropriate sizes for later use.

[0130] For sodium and potassium ion batteries, the only difference is that the active material is replaced with an active material from the corresponding system.

[0131] In addition, an adhesion test was performed on the modified polyethylene oxide obtained in this embodiment, as detailed below:

[0132] (1) The butadiene-functionalized polyethylene oxide was directly adhered to two aluminum foils and fixed at the bonding point for 2 hours with a clip.

[0133] (2) Remove the clamps and fix the two aluminum foils with the unbonded modified polymer side on the universal electronic tensile testing machine. Stretch both ends at a speed of 3 mm / minute.

[0134] The results of the adhesion test are as follows Figure 10 As shown, the entire process is as follows Figure 11 It can be seen that a certain amount of external force is required to separate the two aluminum foils, indicating that the modified polyethylene oxide has excellent adhesive properties. Furthermore, the electrode material prepared using succinic anhydride-functionalized polyethylene oxide as a binder has a smooth surface without obvious defects. Figure 12 .

[0135] Example 6

[0136] This embodiment includes the following steps:

[0137] (I) Catalyst Preparation

[0138] (1) Dissolve 176.3 mg of anhydrous ferric chloride and 301.2 mg of tetrabutylammonium chloride in 2 mL of anhydrous acetonitrile;

[0139] (2) Stir the above mixture in a glove box filled with nitrogen for 25 minutes;

[0140] (3) The solvent of the above solution was rotary evaporated, and the crude product was recrystallized in hexane / ethyl acetate. The recrystallized product was used as the catalyst in the subsequent reaction. The entire reaction process is shown in [reference needed]. Figure 1 .

[0141] (II) Preparation of polyoxyethylene with butadiene nitrile functionalization

[0142] (1) Add 280 mg of raw polyethylene oxide powder (relative molecular weight of 600,000), 102 mg of fumaric acid reactant monomer, and 7.6 mg of catalyst to a 100 mL sealed tube and transfer it to a glove box filled with nitrogen.

[0143] (2) Add 15 mL of anhydrous acetonitrile to the above-mentioned sealing tube in the glove box, seal the sealing tube, and stir until fully dissolved;

[0144] (3) Take out the above-dissolved mixed solution from the glove box and stir it for 12 hours under the illumination of a 390nm LED lamp;

[0145] (4) After the reaction is complete, the above mixed solution is slowly added dropwise to a precipitation bath of anhydrous acetonitrile and diethyl ether at a volume ratio of 1:8 (anhydrous acetonitrile: diethyl ether) for precipitation. The product is collected by filtration, redissolved in 10 mL of anhydrous acetonitrile and precipitated again in the precipitation bath. The above operation is repeated three times. The product is then collected and dried in a vacuum oven at 40°C for 24 hours for later use.

[0146] The modified polyethylene oxide obtained in this embodiment can be used in binders for infinitely variable ceramic materials, such as lithium lanthanum zirconium oxide (LLZO) and alumina. Taking alumina as an example, the specific steps are as follows:

[0147] (1) Mix 80mg of alumina powder and 20mg of functionalized polyethylene oxide powder in a ball mill at a speed of 200 rpm;

[0148] (2) The above mixed powder is filled into the mold and compacted under constant pressure of 300MPa. The compacted inorganic ceramic electrolyte sheet is then taken out for later use.

[0149] The AC impedance of the inorganic ceramic electrolyte membrane using modified polyethylene oxide as a binder was tested as follows:

[0150] (1) Place the modified polymer-bonded alumina sheet in a constant pressure test mold for solid-state batteries, with stainless steel electrodes at both ends, and apply a pressure of 100MPa externally;

[0151] (2) The assembled solid-state battery was subjected to AC impedance testing on an electrochemical workstation.

[0152] The AC impedance spectrum obtained from the test is as follows Figure 13 As shown, the alumina electrolyte sheet bonded with succinic acid-functionalized polyethylene oxide exhibits a lower AC impedance, indicating that succinic acid-functionalized polyethylene oxide can effectively bond inorganic particles and provide good ionic conductivity, ensuring that the entire electrolyte has a smooth ion conduction pathway.

Claims

1. A method for preparing butadionitrile-functionalized polyethylene oxide, characterized in that, Includes the following steps: (I) Preparation of catalysts (1) Dissolve 124.3 ~ 187.5 mg of anhydrous ferric chloride and 205.4 ~ 310.5 mg of tetrabutylammonium chloride in 0.5 ~ 3 mL of anhydrous acetonitrile to obtain a mixed solution; (2) Stir the above mixture evenly under a nitrogen atmosphere; (3) The solvent obtained in step (2) is evaporated by rotary evaporation, and the crude product is recrystallized in hexane / ethyl acetate. The product after recrystallization is the catalyst used in the subsequent reaction. (II) Preparation of polyoxyethylene with butadiene acrylonitrile functionalization (1) Add 220 ~ 440 mg of raw polyethylene oxide powder, 78 ~ 234 mg of fumaric acid reactant monomer, and 4.4 ~ 13.2 mg of catalyst into a sealed tube and transfer it to a nitrogen atmosphere; (2) Add 10 to 50 mL of anhydrous acetonitrile to the sealing tube under a nitrogen atmosphere, seal the tube and stir until fully dissolved to obtain a well dissolved mixed solution; (3) Take out the dissolved mixture and stir it under 390 nm LED light for 2 to 24 hours; (4) After the reaction is completed, the mixed solution obtained in step (3) is added dropwise to a precipitation bath containing anhydrous acetonitrile and diethyl ether at a volume ratio of 1:4 to 8 for precipitation. The product is collected by filtration, redissolved in anhydrous acetonitrile and precipitated again in the precipitation bath. This step is repeated three times. The product is collected and dried, which is the prepared product, butadionitrile-functionalized polyoxyethylene.

2. The method for preparing butadionitrile-functionalized polyethylene oxide according to claim 1, characterized in that, The original polyethylene oxide powder comprises polyethylene oxides with different molecular weights ranging from 100,000 to 2,000,000 relative molecular weights.

3. The application of the butadionitrile-functionalized polyethylene oxide obtained by the preparation method according to claim 1, characterized in that, It is used in solid polymer electrolytes and, depending on the difference in cation salts, is applied in solid lithium, sodium, and potassium ion batteries.

4. The application of the butadionitrile-functionalized polyethylene oxide obtained by the preparation method according to claim 1, as a binder in the preparation of electrodes for lithium, sodium, and potassium ion batteries.

5. The application of the butadionitrile-functionalized polyethylene oxide obtained by the preparation method according to claim 1, as a binder in the process of pressing inorganic ceramic powder with lithium, sodium and potassium ion conductivity into a film.

Citation Information

Patent Citations

  • Preparation method and application of succinonitrile-based double-layer composite polymer electrolyte

    CN113299985A